2020
DOI: 10.1155/2020/8846507
|View full text |Cite
|
Sign up to set email alerts
|

Economic Policy Uncertainty and Stock Returns of Africa: A Wavelet Coherence Analysis

Abstract: This study explores how global economic policy uncertainty (EPU) shocks comove with stock returns (SR) of eight African countries—Botswana, Ghana, Kenya, Morocco, Namibia, Nigeria, South Africa, and Zambia. The study employed daily data from December 2010 to December 2019 using wavelet coherence analysis. The results showed that global EPU comoves with most of the SR of African markets and was concentrated in the longer term, especially during the period between 2011 and 2019, although not substantially. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 45 publications
2
39
0
Order By: Relevance
“…ese policy uncertainties have a significant impact on financial markets and a growing interest in the literature relating to the link between EPU and international financial markets, most especially the stock markets, which have led several researchers to focus on this area. us, studies by Brogaard and Detzel [37], Arouri et al [38], Bahmani-Oskooee and Saha [12], Adam [39], Asafo-Adjei et al [40], and Chiang [41] have demonstrated that heightened uncertainty hurts stock returns. Moreover, Pastor and Veronesi [42], Liu and Zhang [43], Tsai [44], and Jurado et al [19] with different research orientations focus on the impact of uncertainty on stock market volatility and find that the inclusion of EPU can enhance the predictability of stock returns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…ese policy uncertainties have a significant impact on financial markets and a growing interest in the literature relating to the link between EPU and international financial markets, most especially the stock markets, which have led several researchers to focus on this area. us, studies by Brogaard and Detzel [37], Arouri et al [38], Bahmani-Oskooee and Saha [12], Adam [39], Asafo-Adjei et al [40], and Chiang [41] have demonstrated that heightened uncertainty hurts stock returns. Moreover, Pastor and Veronesi [42], Liu and Zhang [43], Tsai [44], and Jurado et al [19] with different research orientations focus on the impact of uncertainty on stock market volatility and find that the inclusion of EPU can enhance the predictability of stock returns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…e real wavelet has v � 1, and the complex wavelet v � 2. e variance of the corresponding variable is denoted by δ 2 x . Following Rua et al [44], we define the cross-wavelet transform of two commodities market series (X) and (Y) as follows:…”
Section: Continuous Wavelet Transform and Waveletmentioning
confidence: 99%
“…Specifically, the study provides new evidence by adjusting for the possible influence of EPU using partial wavelet coherence and wavelet coherence, which is lacking in the comovement of agricultural commodities in previous studies (see, for example,Živkov et al [7]; Amrouk et al [17]). e advantage of the use of wavelet-based methods is well documented in the literature (see [41][42][43][44]). is paper, therefore, investigates the partial correlations in the agricultural commodity prices by including (excluding) the influence of EPU.…”
Section: Introductionmentioning
confidence: 99%
“…Exploring the nature and sources of the relationships has emerged as a promising area in academic research for decades. As a corollary to this, a burgeoning body of literature has examined the relationship between stocks and macroeconomic variables (see, Shi et al, 2021 ; Asafo-Adjei et al, 2020 ). Another strand of studies also explores the behaviours of macroeconomic variables to crude oil market volatilities (for example, see, Salisu et al, 2019 ; Balcilar et al, 2021 ; Ratti and Vespignani, 2016 ).…”
Section: Introductionmentioning
confidence: 99%